1999
DOI: 10.1097/00001756-199911080-00007
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic stimulation in bilateral vestibular failure

Abstract: Bilateral galvanic vestibular stimulation (GVS) with current intensity of 3 mA was applied at mastoid level in 11 patients with chronic bilateral vestibular failure, in order to determine ocular motor responses by 3-D video-oculography. The following abnormal features were found: (1) a predominantly torsional or mixed torsional-horizontal nystagmus at the onset of stimulation with lower current intensities (1.0-3.0 mA) in nine patients; (2) a reduced amplitude of tonic ocular torsion by about 50% in nine patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Also, our results were inconsistent with the findings of MacDougall et al [16] who found overshoot in 100% of healthy subjects (using a 5 mA bilateral stimulation during 300 s). However, they are consistent with the findings of Dieterich et al [17] who described overshoot in 45% of bilateral vestibular failure subjects (using a 3 mA bilateral stimulation during 6 s).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Also, our results were inconsistent with the findings of MacDougall et al [16] who found overshoot in 100% of healthy subjects (using a 5 mA bilateral stimulation during 300 s). However, they are consistent with the findings of Dieterich et al [17] who described overshoot in 45% of bilateral vestibular failure subjects (using a 3 mA bilateral stimulation during 6 s).…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the longer the galvanic stimulus the higher the occurrence of overshoot, which would explain why Dieterich et al [17] observed only 45% of overshoot after 6 s stimuli, whereas MacDougall et al [16] observed 100% after 300 s stimuli. Thus, with a short galvanic stimulus, only subjects with labyrinthine disease will exhibit overshoot, whereas with longer stimulus, normal subjects will also exhibit overshoot.…”
Section: Discussionmentioning
confidence: 99%
“…The VCR is indicative of otolith (saccular) function and can be elicited by highlevel acoustic stimuli (Murofushi et al, 1995;McCue and Guinan, 1994) by mechanically tapping on the forehead (Halmagyi, , 1999 and by galvanic stimulation (Skurczynski and Ernst, 1989;Dieterich et al, 1999;Murofushi et al, 2002;Monobe and Murofushi, 2004). It is widely accepted that the vestibular nerve must be intact (McCue and Guinan, 1997) to carry the information from the saccule (via vestibular nuclei, interneurons) to the motoneurons of the sternocleidoid muscle (SCM) to elicit an EMG response by SCM contraction.…”
Section: Introductionmentioning
confidence: 99%
“…It seems logical to believe that the mechanism of GVS-induced effects in humans is in general analogous. The presence of oculomotor [3] and postural [4] responses to GVS is strictly related to preservation of the function of the vestibular nerves, but does not depend on the functional integrity of the labyrinths. The GVS technique is extensively used in neurophysiological tests in humans because it is simple and practically safe; it also allows experimenters to sufficiently accurately regulate the stimulation intensity.…”
Section: Introductionmentioning
confidence: 93%